Surface Temperature Inversion Analysis in Beijing Municipal Area - Wang, Weijia (Transactions on Environment, Energy and Earth Sciences, 2024)
The urban heat island (UHI) effect means the temperature in the city is significantly higher than that in the peripheral suburbs. It is important to research the UHI effect to understand how human activities affect the urban climate, supporting the reduction of pollution in the urban environment, controlling energy consumption, and improving urban residents’ health. This study takes downtown Beijing as an example and uses Landsat 8 satellite data to analyze the surface temperature inversion by preprocessing the remote sensing images, such as radiometric calibration and atmospheric correction, combined with the vegetation index (NDVI) inversion, and using the surface thermal radiation intensity calculation and the single-window algorithm, to derive the distribution of the surface temperature. Results show that most of the surface temperatures in downtown Beijing are distributed between 21 and 32 degrees Celsius in summer, demonstrating significant spatial variability, especially in the downtown area with higher temperature values, proving that the UHI effect is more significant in the residential areas. This finding validates the high-precision inversion capability of the single-window algorithm in complex urban environments. The study also suggests that the surface temperature inversion can be further improved by introducing more remote sensing data and improving the algorithm in the future.